Structural and Thermodynamic Properties of the High-Entropy Alloy AlCoCrFeNi Based on First-Principles Calculations - Wu, Juefei; Yang, Zhen; Xian, Jiawei; Gao, Xingyu; Lin, Deye; Song, Haifeng (Frontiers in Materials, 2020)
In the past two decades, the high-entropy alloy AlCoCrFeNi has attracted much attention due to its outstanding thermal and mechanical properties under ambient conditions, however, the thermodynamic of this alloy under high temperature and high pressure is relatively insufficient. Combining the similar atomic environment (SAE) based structural modeling method and the modified mean-field potential (MMFP) approach based on the first-principles calculations, we studied the lattice and magnetic structure and thermodynamic properties of the body-centered-cubic AlCoCrFeNi, taking advantages of supercell simulations. AlCoCrFeNi has strong local lattice distortion among 3d high-entropy alloys with the coefficient ∆d= 0.24; the calculated stable ferromagnetic structure at 0 K will transform to the paramagnetic structure at the Curie temperature TC = 279.75 K, which is in good agreement with previous calculations; the calculated equilibrium volumes, bulk modulus and shock Hugoniot all match well the available experimental data and other theoretical results. Our results demonstrate the validity and reliability of our methods used to study the dynamic properties of AlCoCrFeNi, providing a promising scheme for studying the dynamic properties of sophisticated high-entropy alloys.